15. REMARKS ON THE RESULTS OF TRIPOD ACETABULAR HIP REPLACEMENT IN THE TREATMENT OF STAGE IV HIP TUBERCULOSIS AT NATIONAL LUNG HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Introduction: Hip tuberculosis is secondary tuberculosis, accounting for about 15-20% of bone and joint tuberculosis diseases. Hip tuberculosis is a difficult disease to diagnose and treat, especially late-stage hip tuberculosis, which destroys the acetabulum and femoral neck.Objectives: 1) Review the clinical characteristics and diagnostic imaging of patients undergoing Tripod acetabular hip replacement; 2) Review the outcome of total hip replacement with Tripod cup to treat stage IV hip tuberculosis at the National Lung Hospital in 2023.Method: Clinical intervention study without control group.Results: Average age of the study group: 47.2 ± 15.1 years; Gender: Men account for 68.7%;Lesions in the acetabulum of the research group: Type IA had 5 patients (15.6%), type IB had 15 patients (46.9%), type IC had 12 patients (37.5%). 1 year after hip replacement, no patient showed signs of acetabular instability.Conclusion: Hip replacement with a Tripod cup for cases of hip tuberculosis without damage to the medial wall is a good choice, helping to avoid the need for acetabular bone grafting or the use of acetabular augmentations, which increases costs. and risk to patients.
Keywords: Hip tuberculosis, Tripod cup, acetabular defect.